Temperature Monitoring of Heating System for Flexitank - Lurdsuami, Sharon; Mohd Shah, Nor Shahida; Sadun, Amirul Syafiq; Mohd Zahari, Siti Norsyaheeza; Muhammad Rusydi Muhammad Razif (Progress in Engineering Application and Technology, 2022)
This project was created to improve the quality of services and additionally to upgrade the functionality of Flexitank and its heating systems overall. Heating systems in Flexitank helps in maintaining the preferred temperature of the products from the time of transportation to the destination. Thus, A prototype temperature monitoring system was developed to test its proper functionality using hot water. In this way, the workers of Flexitank can notice the increased temperature of the steam and can control its flow by adjusting the temperature. There were several software and hardware equipment were used to build this system, mainly based on Arduino as NodeMCU ESP32, Arduino IDE, and Blynk app to perform tasks of the monitoring system. The NodeMCU ESP32 was interfaced with the respective Type K Temperature Sensor with the installed Blynk app. In a nutshell, it is crucial for building a useful steam temperature monitoring system to obtain greater benefits through the advanced technology of the internet of things (IoT).